Rapeseed meal as an alternative source of vegetable protein - Strashynskyi, Igor; Pasichnyi, Vasyl; Kompanets, Ivan; Kosyuk, Olha (My University, 2023)
The aim of this study was to investigate the structuring potential of RPC-only and RPC-WG mixtures for meat analogue production in a shear cell using different temperatures and ratios of RPC and WG. WG is often used in plant protein mixtures to enhance fiber formation in meat analogues. The structural properties of the product were compared with those from SPC and an SPC-WG mixture by texture analyzer using the uniaxial tensile test. The morphology of the structure was visualized by confocal laser scanning microscopy (CLSM). The air porosity of the sheared product was analyzed by X-ray microtomography (XRT). Метою цього дослідження було дослідити структурний потенціал сумішей лише RPC і RPC-WG для виробництва аналогів м’яса в камері зсуву з використанням різних температур і співвідношень RPC і WG. WG часто використовується в рослинних білкових сумішах для посилення утворення клітковини в м’ясних аналогах. Структурні властивості продукту порівнювали з властивостями SPC і суміші SPC-WG за допомогою аналізатора текстури за допомогою випробування на одноосьовий розтяг. Морфологію структури візуалізували за допомогою конфокальної лазерної скануючої мікроскопії (CLSM). Повітряну пористість виробленого продукту аналізували за допомогою рентгенівської мікротомографії (XRT).
Keywords: кафедра технології м’яса і м’ясних продуктів; rapeseed meal; meat analogue; protein isolate; ріпаковий шрот; аналог м’яса; білковий ізолят